2013
DOI: 10.1088/0004-6256/145/2/37
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Mass Function and the Surface Density Profile of NGC 6231

Abstract: We have performed new wide-field photometry of the young open cluster NGC 6231 to study the shape of the initial mass function (IMF) and mass segregation. We also investigated the reddening law toward NGC 6231 from optical to mid-infrared color excess ratios, and found that the total-to-selective extinction ratio is R V = 3.2, which is very close to the normal value. But many early-type stars in the cluster center show large color excess ratios. We derived the surface density profiles of four member groups, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 57 publications
5
61
0
Order By: Relevance
“…Recently, Brott et al (2011) and Ekström et al (2012) published new stellar evolution models with stellar rotation. The results (age and the IMF) are very similar to each other (see for details Hur et al 2012;Sung et al 2013).…”
Section: Age and Initial Mass Functionsupporting
confidence: 74%
“…Recently, Brott et al (2011) and Ekström et al (2012) published new stellar evolution models with stellar rotation. The results (age and the IMF) are very similar to each other (see for details Hur et al 2012;Sung et al 2013).…”
Section: Age and Initial Mass Functionsupporting
confidence: 74%
“…Since Sung et al (1997) achieved the successful detection of many PMS stars in NGC 2264, this efficient technique has been used to search for PMS members in a series of studies (e.g., Sung et al 1998Sung et al , 2008Sung et al 2013b;Park et al 2000;Park & Sung 2002;Lim et al 2014aLim et al , 2014b. In order to identify Hα emission stars photometrically we have defined the Hα index as Hα − (V I + )/2 .…”
Section: Membership Selectionmentioning
confidence: 99%
“…Previous studies on NGC 1624 have adopted the normal reddening law (R V = 3.1, Chini & Wink 1984;Jose et al 2011), while Pandey et al (2013a showed, from photometric and polarimetric data, that the reddening law toward NGC 1931 is slightly different from that found in the general ISM. In order to check the reddening law toward these clusters we investigated various color excess ratios in the optical and IR passbands as performed in the series of studies (Kook et al 2010;Lim et al 2011;Hur et al 2012;Sung et al 2013b;Lim et al 2014aLim et al , 2014b. Lim et al (2014a) have noted that several mid-late-B-type MS stars in the young open cluster IC 1848 have a bluer color than that of normal B-type MS stars.…”
Section: Reddening and The Reddening Lawmentioning
confidence: 99%
See 2 more Smart Citations